In vitro evaluation of the human gingival fibroblast/gingival mesenchymal stem cell dynamics through perforated guided tissue membranes: cell migration, proliferation and membrane stiffness assay. (8th February 2017) - Gamal, A. Y.; Al‐Berry, N. N.; Hassan, A. A.; Rashed, L. A.; Iacono, V. J.
Abstract : Background: Migration of gingival fibroblasts/gingival mesenchymal stem cells through macro‐perforated barrier membranes may allow them to participate positively in periodontal regeneration. The optimal guided tissue membrane perforation diameter that could favor maximum cell migration into the defect area and at the same time act as an occlusive barrier for gingival epithelium and its associated gingival extracellular matrix component is not yet identified. Material and Methods: Cultured human gingival fibroblasts/gingival mesenchymal stem cells were placed in the upper chambers of 12‐well collagen‐coated polytetrafluoroethylene transwells, which were manually perforated with 0.2, 0.4 and 0.7 mm sized pores. The lower chambers of the transwells received blood clot as an attraction medium. The number of cells that have migrated to the lower chambers was calculated. Proliferation of these cells was evaluated using MTT assay. Scanning electron microscopy images were obtained for the lower surfaces of the transwell membranes. Perforated bovine collagen membranes (Tutopatch ® ) were subjected to mechanical testing to determine the tensile strength and modulus of elasticity. Results: Group 3 (0.7 mm) showed significantly higher values for cell migration and proliferation. All groups showed a small degree of extracellular matrix migration through membrane perforations. Scanning electron microscopy evaluation revealed variable numbers of cells in fibrin matrices located mainly around the pore edges. There were non‐significant differences between groups regarding mechanical properties. Conclusions: The present study demonstrated that macro‐membrane perforations of 0.2, 0.4 and 0.7 mm are suitable pore diameters that could maintain membrane stiffness and allow for cellular migration. However, these membrane perforation diameters did not allow for total gingival connective tissue isolation.